Associations Between Different Dietary Vitamins and the Risk of Obesity in Children and Adolescents: A Machine Learning Approach - Tang, Weifeng; Zhan, Wenqiang; Wei, Mengdan; Chen, Qian (Frontiers in Endocrinology, 2022)
Backgrounds: Simultaneous dietary intake of vitamins is considered as a common and real scenario in daily life. However, limited prospective studies have evaluated the association between multivitamins intake and obesity in children and adolescents. Objectives: This study aimed to evaluate the relationship between the intake of different dietary vitamins and the risk of obesity in children (6-11 years) and adolescents (12-19 years). Methods: We conducted a cross-sectional study based on data from U.S. National Health and Nutrition Examination Survey, 2013-2016. A total of 3634 children and adolescents were included who had available data on dietary vitamins, obesity and covariates. We analyzed the dietary intake levels of nine vitamins, including vitamin A, vitamin B1, vitamin B2, vitamin B6, vitamin B12, vitamin C, vitamin D, vitamin E, vitamin K. Multivariate logistic regression was used to model the associations between vitamins and obesity. Bayesian kernel machine regression (BKMR) was employed to explore the joint and independent effects of vitamins on obesity among children and adolescents. Results: In the multivariate logistic regression model, five vitamins (vitamin A, vitamin B1, vitamin B2, vitamin B12, and vitamin D) were significantly associated with obesity in children and adolescents. BKMR analysis showed that when the concentration of the nine vitamins was at or above the 55th percentile compared with the median value, the combined intake of these vitamins could significantly reduce the risk of obesity in children and adolescents. Potential interactions between vitamin B2 and vitamin B12 in increasing the risk of obesity in children and adolescents were observed. Conclusions: We determine the combined effects of multivitamins on obesity in children and adolescents, and observe a significant interaction between vitamin B2 and vitamin B12. Further cohort studies are needed to clarify the health effects of multivitamins intake in a larger population.